The library and the new challenges of communication. The disoriented librarian - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2014)
Communication with the library user is being changed by the loss of the library´s information monopoly, the dematerialization of the book and the importance of technology in the non-face-to-face relationship. Within the new ways of communication, the ability to become used to tools and devices in a daily and non-work environment is essential. Library professionals must begin to understand the new ways of communication as a balance between the personal and profesional domains.